Professional, Personal, and Relational: Exploring the Salience of Identity in Academic Careers. Issue 3 (2nd July 2016) - Pifer, Meghan J.; Baker, Vicki L.
ABSTRACT: This article explores the role of identity in lived experiences within the professoriate. While scholarship has given some attention to professional identity and personal identity, little in the literature has attempted to present a holistic view of identity and the complex ways that it defines and influences academic careers. The authors present findings from their analysis of interview data from 50 participants across career stages, from doctoral students to full professors. These findings suggest that three distinct but related, and potentially synergistic, components of identity are salient in shaping perceptions of and experiences within academic careers. The authors offer future directions for research centered on a rich conceptualization of identity as critical for understanding faculty development, experiences, and needs.